Posterior hybrid surgery for atlantoaxial dislocation coexisting with multilevel cervical spondylotic myelopathy - Sun, Yan; Ma, Haoning; Zhang, Zhihai; Tan, Mingsheng (Frontiers in Surgery, 2023)
Background To introduce a hybrid surgery of posterior craniovertebral fusion plus subaxial laminoplasty for atlantoaxial dislocation (AAD) coexisting with multilevel cervical spondylotic myelopathy (CSM). Methods A retrospective study was performed by reviewing data from 23 patients with the coexistence of AAD and CSM who underwent the hybrid technique (n = 23). Clinical outcomes, including visual analogue scale (VAS), Japanese Orthopaedic Association (JOA), and neck disability index (NDI) score, and radiological cervical alignment parameters including C0–2 and C2–7 Cobb angle and range of motion (ROM) were analyzed. The operation time, blood loss, surgical levels, and complications were recorded. Results The included patients were followed up with an average of 20.91 months (range, 12–36 months). Clinical outcomes including JOA, NDI, and VAS scores were significantly improved at different postoperative follow-up points. C0–2 Cobb angle, C2–7 Cobb angle, and ROM showed a stable tendency after 1-year follow-up. No major perioperative complications occurred. Conclusion This study underlined the importance of pathologic condition of AAD coexisting with CSM and presented a novel hybrid approach of posterior craniovertebral fusion plus subaxial laminoplasty. This hybrid surgery was effective in achieving the desired clinical outcomes and better maintaining cervical alignment, proving its value and safety as an alternative technique.